Hubungan antara Stress Kerja dengan Kemandirian pada Perawat Rumah Sakit - Rizkiyah Rachmawati; Jimmy Ellya Kurniawan (Universitas Ciputra Surabaya, 2017)
The role of a nurse in undertaking his/her job is considered complex which can lead to a stress; in that case, it leverages his/her performance in the workplace in terms of handling a patient. A survey result shows that 50.9% of nurses working in the hospital in Indonesia encounter job stress. This leads to a numerous physical, psychological, and behavioral symptoms and causes the decrease of work performance. One of work performance indicators is independence; if the work performance decreases, the level of independence will go lower, as well. The support is shown by preceding study stating that there is a negative relation between job stress and independence. As a matter of fact, however, the relation between job stress and independence of the nurses is a non-existent. This study aims at seeking out the relation between job stress and the independence level of nurses in the hospital. The data collected for this quantitative approach study is taken from questionnaires given to 94 nurses. The subject of the study is nurses working in ICU (Intensive Care Unit) and HCU (High Care Unit), IGD, nurse inpatient. The instruments employed in data collection are Decotis’ Organizational Determinants Job Stress (1983) and the modification from Masrun, et al. (1986) regarding the scale of independence. The result showed there is no significant relationship between job stress and independence r = -.051 (r < 0.3) pserta nilai p = 0. 313 (p > 0.05).